Flying Tiger : international relations theory and the politics of advanced weapons - Krotz, Ulrich (New York ; Oxford : Oxford University Press, 2011)
Ulrich Krotz's 'Flying Tiger' takes a relatively obscure episode - the joint Franco-German production of a very expensive military helicopter, the Tiger helicopter - to make a groundbreaking theoretical contribution to international relations scholarship.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Tiger (Attack helicopter) -- Design and construction -- Political aspects -- France; Tiger (Attack helicopter) -- Design and construction -- Political aspects -- Germany; Defense industries -- Political aspects -- France; Defense industries -- Political aspects -- Germany; France -- Foreign relations -- Germany; Germany -- Foreign relations -- France